(untitled) (International Journal of Environmental Sciences, 2024)
Diabetes mellitus is a chronic metabolic disorder characterized by persistent hyperglycemia caused by defects in insulin secretion, insulin action, or both. The global prevalence of type 2 diabetes mellitus continues to rise rapidly, creating a need for effective and patient-friendly drug delivery systems. Vildagliptin, a selective dipeptidyl peptidase-4 (DPP-4) inhibitor, is widely used in the treatment of type 2 diabetes mellitus as it enhances the activity of incretin hormones and improves glycemic control. However, conventional tablet formulations may show delayed disintegration and may not provide rapid onset of action. Therefore, the present study was undertaken to formulate and evaluate fast dissolving tablets (FDTs) of Vildagliptin to enhance dissolution rate, improve patient compliance, and facilitate rapid drug release. Fast dissolving tablets were prepared by the direct compression method using different concentrations of superdisintegrants such as croscarmellose sodium and sodium starch glycolate. Preformulation studies including organoleptic evaluation, solubility testing, melting point determination, physicochemical characterization, UV spectroscopic analysis, and drug–excipient compatibility study using FTIR spectroscopy were carried out to assess the properties of Vildagliptin prior to formulation. The prepared formulations were evaluated for various pre-compression and post-compression parameters. The optimized formulation exhibited satisfactory mechanical strength, rapid disintegration, and improved dissolution characteristics. The results indicated that the developed Vildagliptin fast dissolving tablets provide faster drug release and may offer improved therapeutic effectiveness and better patient convenience compared to conventional oral tablets.